ANALISIS PERANAN FILSAFAT NATURALISME DALAM PEMBENTUKAN PARADIGMA KURIKULUM MERDEKA: ANALISIS PERANAN FILSAFAT NATURALISME DALAM PEMBENTUKAN PARADIGMA KURIKULUM MERDEKA - M, Nanda Adrian.; Ismail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study analyzes the philosophical role of naturalism in shaping the paradigm of the Merdeka Curriculum in Indonesia. The problem addressed is the gap between the ideal values of naturalism—such as experiential learning, contextual development, and learner autonomy—and their practical implementation in schools. The research aims to identify how deeply naturalistic principles are embedded in curriculum design and classroom practices. Using a qualitative library research method, the study critically examines academic literature, educational policies, and previous studies to uncover the ideological foundation of the curriculum. The findings reveal that although the Merdeka Curriculum promotes freedom and student-centered learning, its implementation is still hindered by structural rigidity, limited teacher understanding, and bureaucratic constraints. The study concludes that strengthening philosophical integration and reflective teacher training is essential to realize a more adaptive and humanistic education system